Analisis Informasi Citra Antara Sekuens T2 FRFSE dengan T2 Propeller pada pemeriksaan MRI Cervikal Potongan Axial dengan Pesawat MRI GE Signa 1,5 T - Sri Adhi Lukito; Darmini Darmini; Emi Murniati (Poltekkes Kemenkes Semarang, 2017)
Backgroud:research has been done on the difference of image information for T2 FRFSE sequences and T2PROPELLER in Radiology Installation of General Hospital Dr Moewardi. The aim of this study is to determine THE differences of the image information between T2 FRFSE sequences and T2PROPELLER sequences and determine the best sequence between T2 PROPELLER with T2 FRFSE in cervical MRI examination of Spine Axial Slice.MethodsThis research is a quantitative study with experimental approach in Radiology Installation Dr. Moewardi Hospital. Data is collected on examination MRI Cervical in 15 patients, after a Cervical MRI scanning with sagittal slice T2 FRFSE sequences, and then performed scanning T2 PROPELLER sequences on Axial slice. Presented to the three doctors radiologist to assess. Once the image judged by the three respondents, the data analyse by using SPSS 17.0 with Wilcoxon test.Results:the result showed obtained significance value 0,001 or p value 0,05 Which means that there are differences image information between T2 FRFSE sequences and T2 PROPELLER sequences. Sequens T2 PROPELLER better than sequens T2 FRFSE in MRI CervicalAxial slice.Conclusion:Mean value of the same rank on the anatomy of the vertebral body and the soft tissue of the neck are 5.50 and 4.00 , while the mean rank differently on intraforamen structure is 6.5 , nerve root is 5.56 , so that the spinal cord was 6.15 T2 PROPELLER still better.